Diagnosis of sleepiness, fatigue and depression in patients with myasthenia gravis - O. A. Kreis; T. M. Alekseeva; Yu. V. Gavrilov; P. O. Valko; Yu. Valko (Нервно-мышечные болезни)
Introduction. Examination of excessive daytime sleepiness, fatigue and depression in patients with myasthenia gravis is important for differential diagnosis of other disorders, and adds to a comprehensive clinical assessment.Objective. The aim is a comprehensive assessment of sleepiness, fatigue and depression and evaluation of the impact of autoimmune comorbidity on these symptoms in myasthenia gravis patients, using newly validated Russian versions of international questionnaires. The present article aims at familiarizing a wider Russian-speaking audience of specialists in the field of neuromuscular disease and sleep medicine with the main findings of our previously published work.Materials and methods. The study included 73 patients with MG and 230 control subjects. For sleepiness, fatigue and depression evaluation were used: Fatigue Severity Scale (FSS), Fatigue Impact Scale (FIS) (cognitive / physical / psychosocial subscales), Epworth Sleepiness Scale (ESS), Beck Depression Inventory (BDI) (cognitive-affective and somatic domains), Spielberger–Khanin State Trait Anxiety Inventory (STAI).Results. The Fatigue Severity Scale and Fatigue Impact Scale showed good psychometric properties and can be used to identify distinct aspects of fatigue in patients with myasthenia gravis. The studied patient cohort revealed clinically significant fatigue (69.9 %), excessive daytime sleepiness (15.1 %), moderate to severe depression (20.5 %), a high level of personal (64.4 %) and situational anxiety (27.4 %). Among 13 patients with myasthenia gravis and additional autoimmune comorbidity, there were no significant differences in the severity of sleepiness, fatigue and depression compared with the main group.Conclusion. The use of self-reported scale of sleepiness, fatigue and depression combined with careful clinical-neurological characterization adds to a more comprehensive view of the patient. The identification of sleepiness, fatigue and depression can guide therapeutic decisions and contributes to a better patient care. The presence of concomitant autoimmune pathology in patients with myasthenia gravis does not seem to increase the severity of sleepiness, fatigue and depression.